Оцінка рівномірності розподілу та засміченості зерна при його багаторівневому введенні в пневмосепаруючий канал - Нестеренко, О. В.; Лещенко, С. М.; Васильковський, О. М.; Петренко, Д. І.; Nesterenko, O.; Leshchenko, S.; Vasylkovskyi, O.; Petrenko, D. (ЦНТУ, 2021)
Одним із важливих показників ефективності роботи пневмосепаруючих каналів є рівномірність поля швидкостей повітряного потоку, яка в свою чергу залежить від розподілу зернового матеріалу в робочій зоні сепарації. В статті приведені результати розподілу зернового матеріалу при багаторівневому способі введення зерна, а також його вплив на засміченість легкими домішками по висоті пневмосепаруючого каналу. В результаті досліджень отримано залежності засміченості очищеного зерна легкими домішками від кількості задіяних рівнів живильного пристрою. The uniformity of grain distribution in a pneumatic separation channel is an important factor and it significantly affects the quality of grain cleaning. Indeed, with uneven feeding, impurities entering the pneumatic separating channel, to a large extent, are located in the middle or lower layers of grain flow, which impairs the possibility of their release into the settling chamber. Feeders are used to create a more uniform distribution of grain in the operating area of the pneumatic separating channel. They provide conditions under which grain material is fed into the air stream by a thin layer of directed jet. This feeding can significantly improve the interaction of the components of the input grain material with air, increasing the likelihood of their release, as well as minimize the contact of particles of the grain mixture, which significantly increases the efficiency of air flow. Based on the review and analysis of feeder designs, we have proposed a feeder for multi-level grain introduction. The use of such a feeder can significantly improve the quality of pneumo-separation, but there is a possibility of light impurities in the upper grain layers, which can affect the completeness of the separation of the purified grain. Experimental studies were conducted to determine the effect of multilevel introduction on the content of light impurities in the purified grain along the height of the pneumatic separation channel, as well as to analyze the distribution of grain mixture in the operating separation area. As a result of the conducted research it is determined that the number of involved levels of introduction of the feeding device influences the degree of clogging of the cleared grain, thus, uniformity of distribution of grain improves at increase in quantity of levels. In particular, when using up to 4 levels of the feeder under load qbi = 350 kg/dm·h at each level, the amount of light impurities entering the purified grain is not more than 3% of their total weight in the source material.
Estimation of Uniformity of Distribution and Clogging of Grain at its Multilevel Introduction into the Pneumo-separating Channel
Keywords: пневмосепаруючий канал (ПСК); засміченість; рівномірність розподілу; живильний пристрій; зерновий матеріал; pneumatic separation channel (PSC); clogging; uniformity of distribution; nutrient device; grain material